Differentiated Instruction as A Strategy in Teaching Introduction to the Philosophy of the Human Person (IPHP) for Grade 11 Students - Macaraeg, Rubell M.; Acuavera, Lorna L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The research study aimed to investigate the effectiveness of differen-tiated instruction as a strategy in teaching Introduction to the Philosophy of the Human Person (IHLP) of one hundred sixty-nine (169) students. The researcher followed a prescribed lesson plan and focused on one ob-jective to meet the expected competency using the students Multiple In-telligences in dividing each class into small groups best suited the study.The study utilized a quantitative research method with a descriptive design to assess the effectiveness of differentiated instruction. To deter-mine the performance of the respondents on the pre-test and post-test using the differentiated instruction, quasi-experimental design is utilized to establish a causal relationship between an independent variable, the differentiated instruction and the dependent variable which is the stu-dents’ performance. T-Test and ANOVA is used to identify the significant differences between the pre-test, post-test, and demographic profile.The findings of the study revealed that majority of student-respondents are female adolescents, belong to a middle-income class fam-ily, are body/kinestic, logic/math, and music styled-learners. The stu-dents performed very satisfactory during pre-test. Differentiated instruc-tion as an intervention strategy was applied to tailor instruction to the learning needs of students based on the Pre-test scores and the students performed very satisfactory during post-test. The ANOVA computation revealed a significant difference between the performance of students during pre-test and post-test. However, no significant difference in the pre-test scores of students when grouped according to sex, age, family monthly income and learning style. A significant difference in the post-test scores of students when grouped according to sex was established. The proposed enhancement to intervention strategies aimed for a differ-entiated output.